The role of Wg signaling in the patterning of embryonic leg primordium in Drosophila. - Kubota, K.; Goto, S.; Hayashi, S. (Developmental Biology, 2003)
Cellular interaction between the proximal and distal domains of the limb plays key roles in proximal-distal patterning. In Drosophila, these domains are established in the embryonic leg imaginal disc as a proximal domain expressing escargot, surrounding the Distal-less expressing distal domain in a circular pattern. The leg imaginal disc is derived from the limb primordium that also gives rise to the wing imaginal disc. We describe here essential roles of Wingless in patterning the leg imaginal disc. Firstly, Wingless signaling is essential for the recruitment of dorsal-proximal, distal, and ventral-proximal leg cells. Wingless requirement in the proximal leg domain appears to be unique to the embryo, since it was previously shown that Wingless signal transduction is not active in the proximal leg domain in larvae. Secondly, downregulation of Wingless signaling in wing disc is essential for its development, suggesting that Wg activity must be downregulated to separate wing and leg discs. In addition, we provide evidence that Dll restricts expression of a proximal leg-specific gene expression. We propose that those embryo-specific functions of Wingless signaling reflect its multiple roles in restricting competence of ectodermal cells to adopt the fate of thoracic appendages.